Adoption of TikTok Location Tag Vouchers among Gen Z in the Food & Beverage Sector - Faza Hibatul Haqqi; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
This study investigates Generation Z's intention to use TikTok Location Tag Vouchers in the food and beverage sector. Using an extended Technology Acceptance Model, we examine three predictors: Perceived Economic Benefit, Perceived Ease of Use, and Social Influence. A quantitative survey was conducted among 109 Gen Z consumers in Jakarta who actively use TikTok and have voucher experience. Partial Least Squares Structural Equation Modeling reveals that Social Influence and Perceived Economic Benefit significantly affect intention to use, while Perceived Ease of Use was found to be insignificant. Social Influence emerged as the strongest driver, highlighting the role of peer validation. These findings challenge assumptions about Gen Z's price sensitivity, demonstrating that social factors drive adoption more than technical ease of use. For food and beverage businesses, this suggests prioritizing influencer ecosystem development and social proof over mere interface simplicity. Future research should examine actual redemption behavior and cross-cultural variations.